The Relationship Between Overprotective Parenting and Independence with Adolescents' Self-Identity Status - Alifatun Sajidah, Nida; Insyirah, Yulia; Handayani, Lusi (Lafadz Jaya Publisher, 2024)
This research aims to determine the relationship between overprotective parenting and independence and the self-identity status of teenagers at Muhammadiyah High School, Bantul, Yogyakarta. The subjects in this research were female students in grades 10 to 12 at SMA Muhammadiyah Bantul. This research uses 3 research variables, consisting of 2 independent variables and 1 dependent variable. The data collection method that will be used in this research is the Adolescent Self-Identity Status Scale, Overprotective Parenting Pattern Scale and Independence Scale. The data obtained in this research was analyzed using a multiple regression analysis technique with two predictors using the Statistical Product and Service Solution (SPSS) 16 For Windows computing system program. The results of this study indicate that there is a positive relationship between Overprotective Parenting and Independence with Adolescents' Self-Identity Status. The results of the analysis using regression analysis techniques resulting from the relationship between the three variables obtained R = 0.415 and R2 = 0.172 with a value of p = 0.000 (p <0.01). There is a very significant positive relationship between Overprotective Parenting Patterns and Adolescents' Self-Identity Status, with a correlation of r 0.283 and a significance level of 0.001 (p<0.01). There is a very significant positive relationship between independence and Self-Identity Status in adolescents, with a correlation of r 0.357 and a significance level of 0.000 (p<0.01). The conclusion in this research is that there is a very significant positive relationship between Overprotective Parenting and Independence with the Self-Identity Status of Adolescents at Muhammadiyah High School Bantul, Yogyakarta. Based on the first minor hypothesis, there is a very significant positive relationship between Overprotective Parenting Patterns and the self-identity status of Muhammadiyah Bantul High School students. Based on the second major hypothesis, there is a very significant positive relationship between independence and the self-identity status of Muhammadiyah Bantul High School students.